Intestinal intussusception: a presentation of Crohn’s disease - Pivatto Júnior, Fernando (2014)
A 46-year-old female patient came to consultation complaining of about 4 days’ abdominal pain associated with constipation. The symptoms had been recurrent for 4 months, with periods of improvement and worsening. In addition, anorexia and significant weight loss were present. There had been no change in stool shape. On physical examination, she referred pain upon deep palpation of right lower quadrant, with no pain upon sudden decompression. Admission laboratory tests showed iron deficiency anemia.